Interannual kinetics (2010–2013) of large wood in a river corridor exposed to a 50-year flood event and fluvial ice dynamics - Boivin, Maxime; Buffin-Bélanger, Thomas; Piégay, Hervé (Geomorphology, 2017)
Keywords: Boivin_Maxime

Estimation of large wood budgets in a watershed and river corridor at interdecadal to interannual scales in a cold‐temperate fluvial system - Boivin, Maxime; Buffin‐Bélanger, Thomas; Piégay, Hervé (Earth Surface Processes and Landforms, 2017)
Abstract Large wood (LW) is a ubiquitous feature in rivers of forested watersheds worldwide, and its importance for river diversity has been recognized for several decades. Although the role of LW in fluvial dynamics has been extensively documented, there is a need to better quantify the most significant components of LW budgets at the river scale. The purpose of our study was to quantify each component (input, accumulation, and output) of a LW budget at the reach and watershed scales for different time periods (i.e. a 50‐year period, decadal cycle, and interannual cycle). The LW budget was quantified by measuring the volumes of LW inputs, accumulations, and outputs within river sections that were finally evacuated from the watershed. The study site included three unusually large but natural wood rafts in the delta of the Saint‐Jean River (SJR; Québec, Canada) that have accumulated all LW exported from the watershed for the last 50 years. We observed an increase in fluvial dynamics since 2004, which led to larger LW recruitment and a greater LW volume trapped in the river corridor, suggesting that the system is not in equilibrium in terms of the wood budget but is rather recovering from previous human pressures as well as adjusting to hydroclimatic changes. The results reveal the large variability in the LW budget dynamics during the 50‐year period and allow us to examine the eco‐hydromorphological trajectory that highlights key variables (discharge, erosion rates, bar surface area, sinuosity, wood mobility, and wood retention). Knowledge on the dynamics of these variables improves our understanding of the historical and future trajectories of LW dynamics and fluvial dynamics in gravel‐bed rivers. Extreme events (flood and ice‐melt) significantly contribute to LW dynamics in the SJR river system. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: Boivin_Maxime